2013
DOI: 10.1039/c3cc42396d
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative electrochemical aryl C–C coupling of spiropyrans

Abstract: The isolation and definitive assignment of the species formed upon electrochemical oxidation of nitro-spiropyran (SP) is reported. The oxidative aryl C-C coupling at the indoline moiety of the SP radical cation to form covalent dimers of the ring-closed SP form is demonstrated. The coupling is blocked with a methyl substituent para to the indoline nitrogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 25 publications
6
55
2
1
Order By: Relevance
“…[4b] The second process involving the BOX radical cation is an oxidative C—C coupling toward the molecule dimerization and is easily identified by the appearance of a new reversible redox system around 0.4 V on the back scan. As expected, the CV of reference hybrid 4 clearly shows the result of the dimerization process, which is kinetically favored when any substituent is present on the indoline heterocycle in position 5 …”
Section: Absorption Wavelength Maxima Determined For Each Trans Statesupporting
confidence: 77%
“…[4b] The second process involving the BOX radical cation is an oxidative C—C coupling toward the molecule dimerization and is easily identified by the appearance of a new reversible redox system around 0.4 V on the back scan. As expected, the CV of reference hybrid 4 clearly shows the result of the dimerization process, which is kinetically favored when any substituent is present on the indoline heterocycle in position 5 …”
Section: Absorption Wavelength Maxima Determined For Each Trans Statesupporting
confidence: 77%
“…Ivashenko et al showed subsequently that blocking coupling by methyl-substitution in the para-position prevents dimerization and the oxidative cyclic voltammetry thus becomes reversible (Scheme 21). 149 The blocking of the oxidative coupling by the methyl group demonstrates that the radical character lies predominantly at this position and not the chromene unit (Scheme 22). 148 Dimerization by oxidative coupling was shown later in self-assembled monolayers of nitrospiropyran also.…”
Section: Redox-properties Of Spiropyransmentioning
confidence: 99%
“…The electrochemical oxidation of PRO occurs in the tertiary nitrogen of the aromatic ring resulting in a radical cation. The proposed mechanism is in agreement with the electrochemical oxidation of N,N‐dimethylaniline which also presents a tertiary nitrogen attached to an aromatic ring .…”
Section: Resultsmentioning
confidence: 99%